Հայկական պատմամշակութային արժեքների հանդեպ քեմալականների դիրքորոշման շուրջ (1919–1922 թթ.) - Սեդա Պարսամյան (ՀՀ ԳԱԱ հրատ.)
Кемалисты стали непосредственными наследниками политики младотурок по нейтрализации армянских исторических и культурных ценностей. Одним из препятствий на пути к формированию новой национальной идентичности для кемалистско-республиканского режима были остатки армянского населения, выжившего после Геноцида, и огромное наследие, оставленное армянами.The policy of destruction adopted by the Young Turks regarding the Armenian historical and cultural heritage was continued also by the Turkish Nationalists. On the way to forming a new national identity, one of the obstacles for the Kemalist – Republican regime was the survived remnants of the Armenian population living in Turkey and the huge Armenian heritage left there.
Keywords: History; Armenian Genocide (1915); D History; N Fine Arts; NA Architecture